PEMBUATAN APLIKASI PENDATAAN PEMASOK SAMPAH ANORGANIK DI BANK SAMPAH DESA KEDUNGRINGIN KECAMATAN BEJI, KABUPATEN PASURUAN BERBASIS WEB MENGGUNAKAN METODE PROTOTYPE - Riswandha, Muhammad Noval; Virgita, Agustin Elsa; Falani, Achmad Zakki (SPIRIT, 2024)
Garbage is waste that is produced by households or industries as a result of people’s daily activities. Every time the amount of waste produced by the community increases every day. Kedungringin Hamlet is one of the hamlets in Kedungringin Village, Beji sub-district, Pasuruan Regency. Kedungringin Village is one of the flood-prone villages, because the production of waste increases every day, as a result of the flood many items are washed away by the flood. To control the increase in waste production, effective waste management is needed. One of the activities to minimize the occurrence of flood disasters is the establishment of waste banks that sort inorganic waste. For this reason, it is necessary to design a website-based application to make it easier for admins and users to make transactions at the waste bank. This design uses the prototype method and MySQL database in the process